2013
DOI: 10.1155/2013/412379
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Green Tea in a Randomized Human Cohort: Relevance to Diabetes and Its Complications

Abstract: Epidemiological studies have argued that green tea could mitigate diabetes and its complications. This study investigated the phytophenolic profile of Mauritian green tea and its antioxidant propensity. The effect of green tea on the risk factors: waist-hip ratio, glucose level, arterial pressure, antioxidant status, and alanine aminotransferase (ALT) in prediabetics was assessed. The experimental group consumed 3 cups of green tea daily for 14 weeks followed by a 2-week washout period. The control group follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 57 publications
(53 reference statements)
3
46
0
1
Order By: Relevance
“…And so forth, relate the change in HbA1c concentration to an increase in polyphenols intake. In this case, only 7 (Balzer et al, 2008;Curtis et al, 2012;Fenercioglu et al, 2010;Kudolo et al, 2005;Pan et al, 2007;Toolsee et al, 2013;Vinson et al, 2012) of the trial included in the meta-analysis included polyphenol metabolites analysis or antioxidant capacity assay.…”
Section: Discussionmentioning
confidence: 99%
“…And so forth, relate the change in HbA1c concentration to an increase in polyphenols intake. In this case, only 7 (Balzer et al, 2008;Curtis et al, 2012;Fenercioglu et al, 2010;Kudolo et al, 2005;Pan et al, 2007;Toolsee et al, 2013;Vinson et al, 2012) of the trial included in the meta-analysis included polyphenol metabolites analysis or antioxidant capacity assay.…”
Section: Discussionmentioning
confidence: 99%
“…four with less than or equal to 3-day duration [56][57][58][59], and two with 7-day intervention [60,61]). One study [62] reported data only on mean arterial pressure, rather than SBP and DBP, and therefore was excluded. Two studies [63,64] using overweight and obese participants were also excluded because no data on BP were reported.…”
Section: Study Identificationmentioning
confidence: 99%
“…19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52 Among the 34 studies, 28 were studies with the primary objective of efficacy assessment and six were studies for safety assessment. The subjects were healthy (10 studies), obese (seven studies), cancer patients (five studies) or other (12 studies).…”
Section: Resultsmentioning
confidence: 99%